The effect of beta-glucan supplementation on glycemic control and variability in adolescents with type 1 diabetes mellitus. (November 2020) - Bozbulut, Rukiye; Şanlıer, Nevin; Döğer, Esra; Bideci, Aysun; Çamurdan, Orhun; Cinaz, Peyami
Abstract: Aims: This study aimed to investigate whether supplemental soluble fiber, oat β-glucan, has any effect on glycemic control and variability of adolescents with type 1 diabetes mellitus. Methods: This study was conducted in 30 adolescents with type 1 diabetes mellitus and it consisted of three phases lasting one week. At Phase I, all subjects followed a standard diet program. For Phase II and Phase III, the subjects continued their standard diet program and added natural oat flakes containing 3 g/day and 6 g/day β-glucan, respectively. Glucose levels were monitored by continuous glucose monitoring (CGM). The maximal, minimal, mean and daytime and night blood glucose levels, percentages of glucose values in a target range and below and above a target values were calculated for each of the phases. Premeal, postmeal, peak blood glucose values and peak times of meals were evaluated for each of the phases. Glycemic variability was measured via SD, CV, MAGE, IQR, MODD, LBGI, HBGI, and CONGA parameters. Results: The maximal, mean and daytime and night blood glucose levels were the lowest at Phase III (p < 0.05). Minimal blood glucose levels were the highest at Phase III (p < 0.05). Phase I, II, and III showed similar durations elapsed for Level 2 and Level 1 hypoglycemia, euglycemia, Level 1 and Level 2 hyperglycemia (p > 0.05). Premeal and postmeal blood glucose levels were lowest at Phase III for breakfast, lunch, and overall (p < 0.05). The lowest peak blood glucose levels were detected at Phase III for breakfast, lunch, dinner and overall (p < 0.05). Phase III also showed delayed peaks for all time-points (p < 0.05 for each) compared to other phases. Phase III had significantly lower levels of SD, CV, LBGI, and CONGA levels than those in either Phase I or Phase II (p < 0.05 for each). Conclusion: 6 g/day oat β-glucan have favorable outcomes in glycemic control and variability in adolescents with type 1 diabetes mellitus.